2005
DOI: 10.1037/0022-3514.88.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Schemas and the Learning of Incomplete Networks.

Abstract: Social networks that are missing relations among some of their members--termed incomplete networks--have been of critical theoretical and empirical interest in sociological research on weak ties and structural holes but typically have been overlooked in social psychological studies of network learning. Five studies tested for schematic processing differences in the encoding and recalling of incomplete networks. In Studies 1 and 2, prior knowledge of missing relations facilitated learning an unfamiliar, incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 80 publications
6
123
0
Order By: Relevance
“…Indeed, the self-monitoring literature has generally reported high self-monitors to be positively associated with more central/brokerage positions in their social networks (e.g., Mehra et al, 2001;H. Oh & Kilduff, 2008;Sasovova et al, 2010), although other studies (Janicki & Larrick, 2005;Kalish & Robins, 2006) did not present consistent results tying high self-monitors to social structures.…”
Section: H1mentioning
confidence: 71%
“…Indeed, the self-monitoring literature has generally reported high self-monitors to be positively associated with more central/brokerage positions in their social networks (e.g., Mehra et al, 2001;H. Oh & Kilduff, 2008;Sasovova et al, 2010), although other studies (Janicki & Larrick, 2005;Kalish & Robins, 2006) did not present consistent results tying high self-monitors to social structures.…”
Section: H1mentioning
confidence: 71%
“…People seem not to be very good at seeing structural holes 'from the inside,' unless they already live in a hole-fi lled world. For example, in summarizing several studies (Freeman, 1992;Janicki and Larrick, 2005), he concluded, 'the summary conclusion from Freeman's and Janicik's experiments is that experience matters: people who live in a network that contains structural holes are more likely to recognize the holes in their next networks' (Burt, 2005: 77). …”
Section: Breaking Out Of Clustersmentioning
confidence: 99%
“…Prior research has found that individuals resolve this problem by activating relational schemas, that is, schematic expectations about how a given kind of interpersonal relation is likely to be patterned. Relational schemas help people process -memorize, interpret and recall -information about otherwise overly intricate interpersonal structures (Baldwin, 1992;Janicik & Larrick, 2005;Ridgeway, 2006). Like all cognitive representations, relational schemas do not yield perfectly accurate pictures of reality, and research has documented various systematic biases stemming from schema activation (Freeman, 1992;Kilduff et al, 2008;.…”
Section: Theory People Hold a Linear-ordering Schema To Process Leadementioning
confidence: 99%
“…Existing arguments emphasizing the bandwagon effect explain how employees' attributions of leadership change as a function of the group's emerging consensus, that is, of how many others within the group have come to regard somebody as their leader. We extend these arguments by drawing insights from relational schema theory, a line of cognitive theory that examines the schematic cognitive structures -"relational schemas" -people employ to make sense of their and others' positions in a network of interpersonal relations (Baldwin, 1992;Brashears, 2013;Fiske, 1991Fiske, , 1992Janicik & Larrick, 2005). By providing theoretical depth into how people cognitively represent and respond to the leadership network emerging around them, relational schema theory makes it possible to link an intra-individual cognitive mechanism to the dynamics -formation and erosion -of informal leadership relations within a group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation